(untitled) (Research, Society and Development, 2021)
Introduction: One of the biggest challenges in dental implant surgeries today is the ideal position in which the implants will be installed, that is, the three-dimensional position. The inclination and parallelism in relation to adjacent teeth and other implants must be respected in order to obtain a better distribution of force, thus avoiding fractures, fatigue and bone resorption, in addition to preserving noble anatomical structures. However, nowadays, dentistry is becoming more digital and can now rely on technological equipment, tomographic exams and scanners, which give the possibility to plan the entire surgical process through software, in addition to enabling the production of surgical guides, through 3D printers or milling machines, which will guide the three-dimensional position of the implant. Objective: To demonstrate the importance of the digital planning process in implant surgery, emphasizing guided surgery techniques in implant dentistry, through a case report. Case description: Male patient, 58 years old, ASA I, leucoderma, attended the School Clinic of the Center for Contemporary Dentistry Upgrade, during the Specialization in Periodontics and Implantology, reporting dissatisfaction with his smile, due to several tooth loss. On clinical examination, he noted the presence of periodontal disease in all remaining elements and anterior crossbite. Thus, we opted for the extraction of dental elements and the manufacture of complete dentures on implants, with virtual planning, using a planned surgical guide specific for guided surgery.